ANALYZING THE INFLUENCE OF MOTIVATIONAL FACTORS AS ANTECEDENT VARIABLE ON STUDENTS ENTREPRENEURIAL INTENTION (CASE STUDY ON FACULTY OF ECONOMICS AND BUSINESS STUDENTS SAM RATULANGI UNIVERSITY) - Djibran, Hanifah .; Saerang, David P.E; Tumiwa, Johan . (Universitas Sam Ratulangi, 2018)
Abstract : Entrepreneurship development in the last few years has indeed become an issue of economic institutions ranging from regional, national and even international. There are several motivations for people who would like to reach what they want to achieve. Some of the people say they want to become entrepreneurs because they can make money on their own and set their own rules. This study aims to test the influence of motivational factors as antecedent variables on student’s entrepreneurial intention. Three motivational factors are obtained in this research which are Tolerance for Risk, Need for Achievement, and Self-efficacy. These factors were adapted to explore on student’s perceptions toward entrepreneurial intention, the survey information collected from 100 students of Faculty of Economics and Business Sam Ratulangi University, and the sample used in this research is the students in 6th (student who have already studied entrepreneurship). The results indicate that students have high motivation for involving the tolerance for risk, need for achievement, and self-efficacy conversely influences directly positively and significantly to entrepreneurial intention. For University, should concern about this issues because it has the closest relationship with students life.Keywords: motivational factors, tolerance for risk, need for achievement, self-efficacy, entrepreneurial intention.